Role of NKCC1 and KCC2 in Epilepsy: From Expression to Function - Liu, Ru; Wang, Junling; Liang, Shuli; Zhang, Guojun; Yang, Xiaofeng (Frontiers in Neurology, 2020)
γ-aminobutyric acid (GABA) plays a crucial role in the central nervous system via activating chloride-permeable GABAa receptors (GABAa Rs) and inducing chloride ion (Cl−) flow, which rely on intracellular chloride concentration ([Cl−]i) of the postsynaptic neuron. The Na-K-2Cl cotransporter isoform 1 (NKCC1) and the K-Cl cotransporter isoform 2 (KCC2), two main members of the cation-chloride cotransporters (CCCs), have been implicated in human epilepsy via resetting [Cl−]i by accumulating and extruding Cl−, respectively. Previous studies have shown that expressions and function of NKCC1 and KCC2 in neonatal neurons may reappear in mature neurons under some pathophysiological conditions, such as epilepsy. Although increasing evidence focusing on the expression of NKCC1 and KCC2 has suggested that impaired chloride plasticity may be closely related to epilepsy, neuroelectrophysiological evidences associated with the functions of NKCC1 and KCC2 are more significantly needed to study the mechanism of epileptogenesis. In this review, we aim to build a bridge between expression and function of NKCC1 and KCC2. We will also briefly review the current research status of the expression regulation and function of NKCC1 and KCC2 in the treatment of epilepsy.